2015
DOI: 10.1021/acs.langmuir.5b00015
|View full text |Cite
|
Sign up to set email alerts
|

The Flocculating Cationic Polypetide from Moringa oleifera Seeds Damages Bacterial Cell Membranes by Causing Membrane Fusion

Abstract: A cationic protein isolated from the seeds of the Moringa oleifera tree has been extensively studied for use in water treatment in developing countries and has been proposed for use in antimicrobial and therapeutic applications. However, the molecular basis for the antimicrobial action of this peptide, Moringa oleifera cationic protein (MOCP), has not been previously elucidated. We demonstrate here that a dominant mechanism of MOCP antimicrobial activity is membrane fusion. We used a combination of cryogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 45 publications
(79 reference statements)
6
58
0
3
Order By: Relevance
“…Antimicrobial properties are possibly attributed by 4‐(α‐ l ‐rhamnopyranosyloxy)benzyl isothiocyanate, methyl N‐4‐(α‐ l ‐rhamnopyranosyloxy)benzyl carbamate and 4‐(β‐ d ‐glucopyranosyl‐1 → 4‐α‐ l ‐rhamnopyranosyloxy)‐benzyl thiocarboxamide (Oluduro, Aderiye, Connolly, Akintayo, & Famurewa, ; Padla et al, ); water soluble lectine protein (Coelho et al, ; Ferreira et al, ; Moura et al, ); flocculating cationic polypeptides (Shebek et al, ); niazimicin (Rim et al, 2014); glycosides 4‐(α‐ l ‐rhamnosyloxy)‐benzyl isothiocyanate, 4‐(α‐ l ‐rhamnosyloxy)‐phenylacetonitrile and moringine (Jahn, Musnad, & Burgstaller, ); proanthocyanidins (Maldini et al, ) in seeds; niaziminin, niazinin (Wang, Chen, & Wu, ), and silver nanoparticles (Prasad & Elumalai, ) in leave extract; cardiac glycosides in pods (Arora & Onsare, ); kaempferol, rhamnetin, kaempferitin, isoquercitrin, and pterygospermin in flowers; spirochin and anthonine in roots (Farooq, Rai, Tiwari, Khan, & Farooq, ; Mehta, Shukla, Bukhariya, & Charde, ; Raj, Gopalakrishnan, Yadav, & Dorairaj, ); and aglycon of deoxy‐niazimicine (N‐benzyl, S‐ethyl thioformate) in bark (Nikkon et al, ). It is cleared from previous studies that seeds may also act directly upon microorganisms and showed broader antimicrobial spectrum than other parts of MO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial properties are possibly attributed by 4‐(α‐ l ‐rhamnopyranosyloxy)benzyl isothiocyanate, methyl N‐4‐(α‐ l ‐rhamnopyranosyloxy)benzyl carbamate and 4‐(β‐ d ‐glucopyranosyl‐1 → 4‐α‐ l ‐rhamnopyranosyloxy)‐benzyl thiocarboxamide (Oluduro, Aderiye, Connolly, Akintayo, & Famurewa, ; Padla et al, ); water soluble lectine protein (Coelho et al, ; Ferreira et al, ; Moura et al, ); flocculating cationic polypeptides (Shebek et al, ); niazimicin (Rim et al, 2014); glycosides 4‐(α‐ l ‐rhamnosyloxy)‐benzyl isothiocyanate, 4‐(α‐ l ‐rhamnosyloxy)‐phenylacetonitrile and moringine (Jahn, Musnad, & Burgstaller, ); proanthocyanidins (Maldini et al, ) in seeds; niaziminin, niazinin (Wang, Chen, & Wu, ), and silver nanoparticles (Prasad & Elumalai, ) in leave extract; cardiac glycosides in pods (Arora & Onsare, ); kaempferol, rhamnetin, kaempferitin, isoquercitrin, and pterygospermin in flowers; spirochin and anthonine in roots (Farooq, Rai, Tiwari, Khan, & Farooq, ; Mehta, Shukla, Bukhariya, & Charde, ; Raj, Gopalakrishnan, Yadav, & Dorairaj, ); and aglycon of deoxy‐niazimicine (N‐benzyl, S‐ethyl thioformate) in bark (Nikkon et al, ). It is cleared from previous studies that seeds may also act directly upon microorganisms and showed broader antimicrobial spectrum than other parts of MO.…”
Section: Resultsmentioning
confidence: 99%
“…The coagulation efficacy of MOCP is observed to be increased with an increase in the initial turbidity of water (Katayon et al, ). Owing to amphiphilic properties, MOCP integrate into the bacterial membranes and are specifically kill several microorganisms, including waterborne pathogens (Shebek et al, ). The seed contain polypeptides, a coagulant, used to treat river water with suspended solid particles and groundwater (Lijesh & Malhotra, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, as the primary structures of all Mo -CBPs proteins are very similar, it was not possible to predict the Mo -CBP 2 sequence. For instance, it was reported that the flocculent peptides MOCP 2.1 and MOCP 2.2 are distinguished by a single amino acid residue (Shebek et al, 2015). Similar situation might occur with Mo -CBP 2 and other M. oleifera proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The flocculation cationic polypeptide showed antibacterial activity by damaging bacterial cell membranes and causing fusion between membranes. Also, it has been used widely in water purification processes [24]. Structure-function studies of Flo peptides revealed that a sequence prone to form a helix-loophelix structural motif is important to the bactericidal activity and the hydrophobic proline residues within the protruding loop are essential for maintaining bactericidal activity [25].…”
Section: Antibacterial Activities Of Moringa Oleiferamentioning
confidence: 99%